Effects of short-term water velocity stimulation on the biochemical and transcriptional responses of grass carp (Ctenopharyngodon idellus) - Tingting Shu; Tingting Shu; Yan Chen; Yan Chen; Yan Chen; Kan Xiao; Kan Xiao; Hongtao Huang; Hongtao Huang; Jingyi Jia; Zhaoxi Yu; Zhaoxi Yu; et al. (Frontiers in Physiology, 2023)
Since 2011, ecological operation trials of the Three Gorges Reservoir (TGR) have been continuously conducted to improve the spawning quantity of the four major Chinese carp species below the Gezhouba Dam. In particular, exploring the effects of short-term water velocity stimulation on ovarian development in grass carp (Ctenopharyngodon idellus) is essential to understand the response of natural reproduction to ecological flows. We performed ovary histology analysis and biochemical assays among individuals with or without stimulation by running water. Although there were no obvious effects on the ovarian development characteristics of grass carp under short-term water velocity stimulation, estradiol, progesterone, follicle-stimulating hormone (FSH), and triiodothyronine (T3) concentrations were elevated. Then, we further explored the ovarian development of grass carp under short-term water velocity stimulation by RNA sequencing of ovarian tissues. In total, 221 and 741 genes were up- or downregulated under short-term water velocity stimulation, respectively, compared to the control group. The majority of differentially expressed genes (DEGs) were enriched in pathways including ABC transporters, cytokine-cytokine receptor interaction, ECM-receptor interaction, and steroid hormone biosynthesis. Important genes including gpr4, vtg1, C-type lectin, hsd17b1, cyp19a1a, cyp17a1, and rdh12 that are involved in ovarian development were regulated. Our results provide new insights and reveal potential regulatory genes and pathways involved in the ovarian development of grass carp under short-term water velocity stimulation, which may be beneficial when devising further ecological regulation strategies.